Skrypal Ivan Gavrylovych. In memory of the scientist - Tokovenko, I.P.; Токовенко, І.П. (PH "Akademperiodyka" of the NAS of Ukraine, 2026)
On November 27, 2025, at the age of 86, Ivan Gavrylovych Skrypal, Doctor of Biological Sciences, Professor, Corresponding Member of the National Academy of Sciences of Ukraine, Honored Worker of Science and Technology of Ukraine, and Laureate of the State Prize of Ukraine in Science and Technology, passed away. The passionate heart of the outstanding microbiologist stopped beating.